Percepção da sexualidade em mulheres submetidas à histerectomia total e subtotal - Faleiros, Nayara de Paula [UNIFESP] (2011)
Hysterectomy is one of the most performed surgeries in many contries, including Brazil. Nevertheless, there is still controversy about the possible psychological effects that can be triggered in female sexuality from this intervention. Depressive symptoms, feelings of loss of femininity, frigidity, change in body image (perceiving themselves hollow, empty, with a hole), and affective interference in conjugal life are some of the aspects found in studies relevant to the topic. Another important issue is related to possible differences in postoperative outcome between total and subtotal hysterectomy. The aim of this research was to investigate the possible effect of preoperative and postoperative (3 and 6 months after surgery) hysterectomy on patients’s sexuality and corporeality. Patients were submitted individual interviews and to Female Function Index (FSFI) and Female Sexuality Questionnaire Mccoy. Symptom relief in preoperative period improved the quality of patient’s life, including sexuality. Three months after postoperative period, strange body sensation was reported which gradatively disappeared. The postoperative period was improved as patients did not attribute to the uterus the source of feminility. A tendency of improvement of sexual life in postoperative period was observed. In conclusion, sexuality has a multifactorial nature and not restricted to a single factor, as hysterectomy. Additional studies are warranted to validate these results.